Chrysin ameliorates synovitis and fibrosis of osteoarthritic fibroblast-like synoviocytes in rats through PERK/TXNIP/NLRP3 signaling - Ding, Liang; Liao, Taiyang; Yang, Nan; Wei, Yibao; Xing, Runlin; Wu, Peng; Li, Xiaochen; Mao, Jun; Wang, Peimin (Frontiers in Pharmacology, 2023)
Objective: Synovitis and fibrosis are common pathological features of knee osteoarthritis (KOA). The interaction of synovitis and fibrosis can promote KOA progression. Chrysin (CHR), a natural flavonoid, may treat inflammation and prevent fibrosis. However, the effect and mechanism of CHR in KOA synovitis and fibrosis remains unclear. Methods: The KOA model was established in male SD rats by anterior cruciate ligament transection (ACLT), and histological analysis was used to evaluate synovitis and fibrosis. IL-6, IL-1β and TNF-α mRNA expression in synovial tissue was measured by qRT‒PCR. Immunohistochemistry (IHC) was performed to detect GRP78, ATF-6 and TXNIP expression in vivo. Synovial fibroblasts (SFs) were treated with TGF-β1 to stimulate the inflammatory response and fibrosis. CCK-8 assays were used to detect the viability of CHR-treated SFs. The IL-1β level was detected by immunofluorescence analysis. Coimmunoprecipitation (Co-IP) and double immunofluorescence colocalization were used to detect the physiological interaction between TXNIP and NLRP3. The expression of fibrosis-related mediators and PERK/TXNIP/NLRP3 signaling molecules was detected by western blotting and qRT-PCR. Results: Four weeks after CHR treatment, pathological sections and associated scores showed that CHR improved synovitis and fibrosis in the ACLT model. In vitro, CHR attenuated the TGF-β1-induced inflammatory response and fibrosis in SFs. Moreover, CHR suppressed the expression of synovial fibrosis markers and PERK/TXNIP/NLRP3 signaling molecules in the synovial tissue of rats with ACLT and cultured SFs. More importantly, we found that CHR inhibited TXNIP-NLRP3 interactions in TGF-β-induced SFs. Conclusions: Our findings indicate that CHR can ameliorate synovitis and fibrosis in KOA. The underlying mechanism may be related to the PERK/TXNIP/NLRP3 signaling pathway.